PEDAGOGUES AND TAES AT COLÉGIO PEDRO II - Historical and Identitarian Notes. - Alessandra Pio (Departamento de História - Colégio Pedro II, 2016)
The article aims at relating the process of development of a professional identity among pedagogues in Brazil, the historical path of Pedagogy as a course, the educational legislation in Brazil and Colégio Pedro II. Colégio Pedro II is an educational institution of excellence, whose history, of national importance, has dealt very little with working relationships outside the classroom. For this reason, the objective of this study is to promote discussions which, regarding professional identities, take into consideration not only the subject, but also the group to which they belong. In terms of theoretical support, the author relies on the sociological approach discussed by Dubar (2005) and the analysis of the history of pedagogy courses carried out by Silva (2006). In addition, other relevant instances are public selection notices for admission to Colégio Pedro II from 1946 to 2015, academic studies upon the theme and responses from entities and professionals in the field of Education upon the pedagogy course programmes. The author takes into account that identities of both the pedagogue and the educational matters technician (TAE) are entangled at institutional level, which shows that the institution is still unsure of what to require and demand from both professionals. Although these educational matters professionals have licentiate degrees in other areas, it is still expected at institutional level that they act as specialists in education (pedagogue).